Treatment of a Case of Toe Hair-Thread Tourniquet Syndrome With Hirasè Technique. Issue 10 (October 2021) - Tamborini, Federico; Sallam, Davide; Maggiulli, Francesca; Pellegatta, Igor; Corno, Martina; Cherubino, Mario; Valdatta, Luigi
Abstract: Hair-thread tourniquet syndrome (HTTS) is an uncommon condition that affects mostly babies, usually a few months old. It happens when a strand of hair or cloth fiber encircles an appendage causing a condition of total or subtotal ischemia ( West J Med 1976;125:335–336). This condition has been described several times in the recent literature. Appendages involved include toes, fingers, genitalia, uvula, and neck ( N Engl J Med 1965;273:866–867). The mechanism of injury usually involves the fiber cutting the skin deeply through soft tissues, veins, and arteries. As HTTS occurs in small babies and hidden parts of the body, sometimes this event can be very difficult to detect and irritability may be the only symptom. The treatment consists of releasing the circumferential constriction and restoring the arteriovenous flow also with microsurgical techniques if vessel interruption is present. Unfortunately, the fiber or the thread often penetrates so deep that, once an HTTS is recognized, it may be very challenging to identify and trim. The authors present a case of HTTS of the second toe of the right foot in a 2-month-old baby treated with surgical release and Hirasè technique. After the thread was successfully cut and removed, the forefoot was covered with aluminum foil, and a bag with ice was immediately put all around. After 3 days, we observed a complete survival of the toe without any sign of necrosis. Later control at 6 months showed complete restitutio ad integrum of the affected digit with a normal perfusion and absence of any onychopathy. Hirasè technique represents a simple, safe, and low-cost option of treatment for HTTS.